Activity-induced phase transition in a quantum many-body system - Kyosuke Adachi; Kazuaki Takasan; Kyogo Kawaguchi (Physical Review Research, 2022)
A crowd of nonequilibrium entities can show phase transition behaviors that are prohibited in conventional equilibrium setups. An interesting question is whether similar activity-driven phase transitions also occur in pure quantum systems. Here we investigate a classical anisotropic lattice gas model that undergoes motility-induced phase separation and extend the model to the quantum regime. The resulting model is a quantum many-body model that undergoes quantum phase transitions induced by non-Hermiticity. The quantum phase diagram includes active phase transitions involving phase separation, microphase separation, and flocking. The quantum phase transitions are identified as the transitions of dynamical paths in the classical kinetics upon the application of biasing fields. Our approach sheds light on the useful connection between classical nonequilibrium kinetics and non-Hermitian quantum physics.